Development Of Urban Legend-Based Story Jumper Media To Enhance Elementary School Students’ Numeracy Skills - Sumartono Sumartono; Timbul Yuwono; Rahaju Rahaju; Nensy Megawati Simanjuntak (Lembaga Riset dan Inovasi Almatani, 2026)
The development of literacy and numeracy competencies is a primary concern in elementary education, particularly in fostering students’ ability to understand, interpret, and apply mathematical concepts in everyday contexts. However, numeracy learning in elementary schools is often presented through conventional approaches that lack contextual and culturally relevant learning resources. Integrating local cultural narratives, such as urban legends, into digital learning media offers an innovative strategy to enhance students’ engagement and numeracy skills. Therefore, this study aimed to develop a Story Jumper-based learning media utilizing urban legend content to improve elementary school students’ numeracy abilities. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants involved elementary school students, teachers, and expert validators. Data were collected through validation sheets, observation, questionnaires, and numeracy tests. Quantitative data were analyzed descriptively, while qualitative data were examined through content analysis. The findings revealed that the developed Story Jumper media met the criteria of validity, practicality, and effectiveness. Expert validation indicated that the media was highly feasible for classroom implementation. The practicality assessment demonstrated positive responses from both teachers and students regarding usability, attractiveness, and accessibility. Furthermore, the effectiveness test showed a significant improvement in students’ numeracy performance after using the media. The integration of urban legend narratives provided meaningful contexts that facilitated students’ understanding of numerical concepts and problem-solving processes. In conclusion, the Story Jumper-based urban legend media is a valid, practical, and effective learning resource for enhancing numeracy skills among elementary school students. The media also contributes to preserving local cultural heritage while supporting innovative digital learning practices in primary education.